IMPLEMENTASI METODE READING ALOUD UNTUK MENGEMBANGKAN KETERAMPILAN BERBAHASA ANAK USIA DINI 5-6 TAHUN DI KELAS B TK NEGERI 2 MANDASTANA - Lestari, Suci; Nisa, Uswatun; Zulkarnaen, Muhammad; Baiti, Noor (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the importance of developing early childhood language skills as a foundation for communication development and learning readiness. A preliminary study in Class B at TK Negeri 2 Mandastana revealed that some children lacked focus while listening to stories, hesitated to express their opinions, and faced difficulties in retelling story content. This study aims to describe the implementation of the "read-aloud" method in developing the language skills of children aged 5–6 years in Class B at TK Negeri 2 Mandastana. A qualitative approach with a descriptive design was employed. The research subjects consisted of one homeroom teacher and eleven children from Group B. Data collection techniques included observation, interviews, and documentation, while data analysis utilized the Miles and Huberman model, comprising data reduction, data display, and conclusion drawing. The results indicate that the read-aloud method was implemented through planning, execution, and evaluation stages integrated into learning activities. This method effectively fostered the children's language skills, evidenced by their ability to answer questions, retell stories, express opinions, use new vocabulary, communicate with teachers and peers, and speak confidently in front of the class. Factors supporting implementation included the teacher's competence, the children's enthusiasm, and the use of media and play-based activities; conversely, inhibiting factors included the children's limited attention spans, varying language abilities, and a lack of sufficient learning media